Effects of music during exercise in different training status - Baldari, C.; Macone, D.; Bonavolonta, V.; Guidetti, L. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: This study examined the interaction of exercise and music to establish the impact of these factors on state-anxiety and time to exhaustion comparing trained and active participants. METHODS: Twenty-six university students (13 trained, 13 active) completed the State-anxiety Inventory questionnaire before and after a submaximal treadmill running until volitional exhaustion in both music and no-music condition. RESULTS: ANOVA showed that both trained and active groups significantly reduced their State-Anxiety scores after exercise tasks (P<0.01, partial h2=0.26) independently by the presence of music. Finding also revealed that active group reported a higher significant reduction of their state anxiety score after exercise in music condition compared to no-music task (P<0.05, d=0.80), while this effect in trained group was not significant. Moreover, data showed that only active-subjects significantly prolonged their exercise experience in presence of music (P<0.05, d=0.47), while trained group did not. CONCLUSION: This study supports the general finding that exercise is associated with state-anxiety reduction, and suggests that music during exercise may improve this effect in active but not in trained participants. Further, listening to music during exercise may prolong the participants` exercise experience but different training status seems to qualify differently this response.